Research Progress on the Performance Enhancement Technology of Ice-on-Coil Energy Storage - Xinxin Guo; Xiaoyu Xu; Zhixin Wang; Zheshao Chang; Chun Chang (Energies)
Ice-on-coil energy storage technology has been widely used in air conditioning systems and industrial refrigeration as an efficient energy storage technology. This paper reviews the research progress of ice-on-coil energy storage technology, including its working principle, system design, key parameter optimization, and practical application challenges and solutions. Three kinds of ice melting systems are introduced. The internal ice melting system has the largest cold storage density and the slowest rate of ice melting. The external ice melting system has the lowest cold storage density and the fastest rate of ice melting. The combined ice melting system can have the highest density of cold storage density and a high rate of ice melting. By comparing the results of different studies, the influence of fin and thin ring application on the heat transfer enhancements of the ice-on-coil storage system is summarized. It is found that the ice storage time can be reduced by 21% and 34% when the annular fin and thin ring are set. Regarding system control, adopting the ice-melting priority strategy increases operating energy consumption, but the economy improves; using the unit priority strategy lowers operating energy consumption, but the economy suffers slightly. When the cooling demand exceeds the cooling capacity of the chiller, an ice melting priority control strategy is more economical. Some suggestions for future research are presented, such as optimizing the shape and arrangement of coil fins and ice storage systems integrated with renewable energy. It provides guidance for the further development of ice storage air conditioning technology.